Rules of Procedure for Deciding Disputes on the Constitutional Authority of State Institutions by the Constitutional Court - Sri Wahyuni (JUSTICES: Journal of Law, 2023)
This study aims to describe one of the powers possessed by the Constitutional Court, namely resolving disputes over authority between state institutions. The type of research  used is a type  of library  research (literature), with  a normative juridical approach method  or doctrinal legal research, namely legal research whose data sources come from secondary data in the form of laws and regulations, books, and journals related to the focus of the problem.  Law No. 24 of 2003 on the Constitutional Court does not explain the details of the authority of  the Constitutional Court . Therefore, the Court  of Justice is empowered to form a regulation to support the smooth performance of its duties and authorities relating to the authority to decide disputes between state institutions. Based on this, PMK No.  08/PMK/2006 on Guidelines for Beracara in Disputes over the Constitutional Authority of State Institutions. When viewed in the formulation of  the 1945 Constitution, the institutions that can be both petitioners and respondents in constitutional disputes  of state institutions are state institutions whose authority is granted by the 1945 Constitution. The formulation of state institutions whose authority is granted by the 1945 Constitution gives rise to multiple interpretations, thus causing differences in the determination of which state institutions can be parties to the dispute. Regardless, however, determining which state institutions can be parties to constitutional disputes between state institutions remains with the Constitutional Court.